On the classification of dysplastic coxarthrosis in adults - Loskutov, Oleksandr; Zub, Tatyana; Loskutov, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
This article deals with the problem of choice of classification for dysplastic coxarthrosis in adults from the position of hip arthroplasty. The performed analysis shows that classification of Crowe J.F. et al. assesses only cranial displacement of the femoral head. The systematization of Hartofilakidis G. et al. separates true and false acetabulum. The classification of Kerboul M. et al. is hardly suitable for arthroplasty. The classifications of Mendes D.J. et al. and Gaston M.S. et al. are of some interest, but no examples of their practical application were found. The application of the AAOS classification of revision defects in dysplastic coxarthrosis is restricted. The classification of Eftekhar N.S. et al. describes the essence of the process of acetabular dysplasia most completely; this classification is suggested for broad application by Ukrainian orthopaedists.